Developing the UNPAD SAS (Universitas Padjajaran Statistical Analysis Series) Software - Ratna Jatnika; Mustofa Haffas; Hendriati Agustiani (SISFORMA, 2018)
Student in Faculty of Psychology think that Statistics is very difficult for them, because Statistics is viewed as a hard science than Psychology which is viewed as a soft science. Various attempts have been made to improve student attitudes toward statistics, so that student have more positive attitudes. One of the efforts is to transform the curiculum of Statistics in Faculty of Psychology UniversitasPadjadjaran by adding SPSS (Statistical Packages for Social Sciences) practicum courses since 2009. There are a variety of data analysis contained in SPSS can be used for data processing. However, there are still some statistical data analysis used by students of the Faculty of Psychology that is not available in SPSS. The aimed of this research is to develop software namely UniversitasPadjadjaran Statistical Analysis Series, which is statistical data analysis software that consist analysis that does not exist in SPSS or other data analysis software. In this preliminary research, modules are developed only for Database Management and Descriptive Statistics.The software development will be carried out by (SDLC = Software Development Life Cycle). SDLC is a series of step or phase that presents a model for development and lifecycle management software or applications.The resulting software is tested on 144 students in Psychology Faculty in UniversitasPadjadjaran. The trial results showed that the software is most appropriate and "user friendly" software.